Differences among peritoneal and pleural mesothelioma: data from the Lombardy Region Mesothelioma Register (Italy) / Differenze fra i mesoteliomi pleurici e peritoneali: dati dal Registro Mesoteliomi Lombardia (Italia) - Mensi, C.; Bonzini, M.; Macchione et al., M. (La Medicina del Lavoro, 2011)
Summary Background: The relationship between asbestos exposure and peritoneal mesothelioma (PEM) is under investigation. Some authors suggest that the association could be weaker than that observed for pleural mesothelioma (PLM). Objective: To compare individual, clinical and exposure characteristics of peritoneal and pleural mesothelioma cases that occurred in the Lombardy Region (Italy). Methods: Cases were drawn from the regional mesothelioma registry (base population >9 million). We selected all PEM cases diagnosed between 2000 and 2007 (N=110) and all PLM cases that occurred between 2000 and 2001 (N=515). Asbestos exposure data (occupational, environmental/familial, or both) were collected by a standardized and validated questionnaire administered to each case or case’s relative. Based on available chest CT scans, we also investigated the concomitant presence of asbestosis and/or pleural plaques as markers of asbestos exposure. Results: PEM and PLM cases had similar proportions of occupational (around 60%) and environmental/familial (7%) asbestos exposure. The proportion of PEM subjects with co-existent occupational and environmental/familial exposures was, however, twice as high as PLM cases (6.1% vs 3.1%). Asbestosis and pleural plaques were more frequent in PEM than in PLM cases (7.7% and 20.9% vs 0.4% and 12.1%, respectively). No differences were detected for duration of exposure and latency among occupationally exposed cases. Conclusion: Our findings from a population-based Registry suggest that high cumulative asbestos exposures are the main risk factors not only for pleural but also for peritoneal mesothelioma.